2018
DOI: 10.4314/star.v5i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Teacher’s knowledge towards Attention Deficit/Hyperactivity Disorder (ADHD) and its associated factors in Nekemte town, Oromiya Region, Western Ethiopia

Abstract: Article InformationThe work of the teacher becomes much more demanding when some learners have AttentionDeficit/Hyperactivity Disorder (ADHD), as their problems with attention span, impulse control and activity level frequently interfere with activities in the classroom and socially. This study revealed the teachers good knowledge about ADHD but about 43.7% of primary school teachers had poor knowledge. The objective of the study was to assess the primary school teacher's knowledge and misconceptions of ADHD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
2
2
1
Order By: Relevance
“…On the other hand, the current finding was lower than studies conducted in Canada 68%, Colombia 48.52%, Saudi Arabia 58.9%, another Saudi Arabia study 72%, India 49%, and South Africa 78%, [ 8 , 9 , 12 , 27 , 28 , 33 , 34 , 46 ]. The discrepancy could be attributed to educational curricula that were used to teach teachers and the highest educational level attained was observed [ 8 , 9 , 12 , 27 , 28 , 33 , 34 , 46 ].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…On the other hand, the current finding was lower than studies conducted in Canada 68%, Colombia 48.52%, Saudi Arabia 58.9%, another Saudi Arabia study 72%, India 49%, and South Africa 78%, [ 8 , 9 , 12 , 27 , 28 , 33 , 34 , 46 ]. The discrepancy could be attributed to educational curricula that were used to teach teachers and the highest educational level attained was observed [ 8 , 9 , 12 , 27 , 28 , 33 , 34 , 46 ].…”
Section: Discussioncontrasting
confidence: 88%
“…The study evidenced that the higher odds of having Good knowledge were observed among participants of the internet user. The same has been reported [ 34 ]. This might be due to the fact that using the internet is a good way of acquiring knowledge and new ways of learning environment for most teachers since it is rapid, cost-effective, get reliable information and publications which enhance knowledge [ 50 53 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Less than 10% of the teachers in our survey thought mistakenly that children with ADHD have an inflexible adherence but special education given to these children’s change their obedience. These particular findings are consistent with the findings of previous studies done by Canu and Mancil, Ghanizadeh et al and few more authors of similar studies [2124].…”
Section: Discussionsupporting
confidence: 94%